Fabrication and assessment of potent anticancer nanoconjugates from chitosan nanoparticles, curcumin, and eugenol - El-Sherbiny, Mohsen M.; Elekhtiar, Rawan S.; El-Hefnawy, Mohamed E.; Mahrous, Hoda; Alhayyani, Sultan; Al-Goul, Soha T.; Orif, Mohamed I.; Tayel, Ahmed A. (Frontiers in Bioengineering and Biotechnology, 2022)
In cancer management and control, the most challenging difficulties are the complications resulting from customized therapies. The constitution of bioactive anticancer nanoconjugates from natural derivatives, e.g., chitosan (Ct), curcumin (Cur), and eugenol (Eug), was investigated for potential alternatives to cancer cells’ treatment. Ct was extracted from Erugosquilla massavensis (mantis shrimp); then, Ct nanoparticles (NCt) was fabricated and loaded with Cur and/or Eug using crosslinking emulsion/ionic-gelation protocol and evaluated as anticancer composites against CaCo2 “colorectal adenocarcinoma” and MCF7 “breast adenocarcinoma” cells. Ct had 42.6 kDa molecular weight and 90.7% deacetylation percentage. The conjugation of fabricated molecules/composites and their interactions were validated via infrared analysis. The generated nanoparticles (NCt, NCt/Cur, NCt/Eug, and NCt/Cur/Eug composites) had mean particle size diameters of 268.5, 314.9, 296.4, and 364.7 nm, respectively; the entire nanoparticles carried positive charges nearby ≥30 mV. The scanning imaging of synthesized nanoconjugates (NCt/Cur, NCt/Eug, and NCt/Cur/Eug) emphasized their homogenous distributions and spherical shapes. The cytotoxic assessments of composited nanoconjugates using the MTT assay, toward CaCo2 and MCF7 cells, revealed elevated anti-proliferative and dose-dependent activities of all nanocomposites against treated cells. The combined nanocomposites (NCt/Eug/Cur) emphasized the highest activity against CaCo2 cells (IC50 = 11.13 μg/ml), followed by Cur/Eug then NCt/Cur. The exposure of CaCo2 cells to the nanocomposites exhibited serious DNA damages and fragmentation in exposed cancerous cells using the comet assay; the NCt/Eug/Cur nanocomposite was the most forceful with 9.54 nm tail length and 77.94 tail moment. The anticancer effectuality of innovatively combined NCt/Cur/Eug nanocomposites is greatly recommended for such biosafe, natural, biocompatible, and powerful anticancer materials, especially for combating colorectal adenocarcinoma cells, with elevated applicability, efficiency, and biosafety.